Technology Based Financial Services Innovation, Financial Literacy and Its Impact on Financial Behavior - Ekaningtyas Widiastuti (Faculty of Economics and Business, Jenderal Soedirman University, 2021)
Information technology grows rapidly and has brought tremendous benefits to the advance of human civilization. People in Indonesia are well known with their quick adaptation ability to any changes including changes in information technology, such as in utilizing available financial services. University students as millennial generation cannot be separated from technology in all aspects including finance. Innovative technology-based financial services (Fintech) provide flexibility for the community, including students, to meet their needs. Financial knowledge and understanding will influence a person in making decisions and behaving appropriately related to effective and efficient financial management. This research focused on students at different universities in Purwokerto, to examine the impact of technology-based financial service innovation and financial literacy on student financial behavior. Questionnaire was used as the data collection method. Convenience sampling was used as the sampling technique and multiple linear regression used as data analysis in this study. The results showed that Social Demography, Financial Socialization and Fintech had no influence on financial behavior. Financial Knowledge and Financial attitude had a positive influence on financial behavior.